Icariin induces osteogenic differentiation of bone mesenchymal stem cells in a MAPK‐dependent manner. (13th April 2015) - Wu, Yuqiong; Xia, Lunguo; Zhou, Yuning; Xu, Yuanjin; Jiang, Xinquan
Abstract Objectives Icariin, a flavonoid isolated from Epimedium pubescens, has previously been identified to exert beneficial effects on preventing bone loss and promoting bone regeneration. However, molecular mechanisms for its anabolic action have, up to now, remained largely unknown. Materials and methods Effects of icariin on cell proliferation and osteogenic differentiation of rat bone mesenchymal stem cells (BMSCs) were systematically evaluated. To characterize underlying mechanisms, its effects on mitogen‐activated protein kinase (MAPK) signalling pathways were determined. Results Results showed that icariin might not have enhanced effects on cell proliferation. However, it seemed to significantly enhance osteogenic differentiation of BMSCs, demonstrated by increasing alkaline phosphatase (ALP) activity and gene expression of collagen type I (Col I), osteocalcin (OCN) and osteopotin (OPN). It was demonstrated that icariin rapidly phosphorylated extracellular signal‐regulated kinase (ERK), p38 kinase and c‐Jun N terminal kinase (JNK). Furthermore, icariin‐stimulated osteogenic effects on BMSCs were dramatically attenuated by treatment with either specific ERK inhibitor of PD98059, p38 inhibitor of SB202190 or JNK inhibitor SP600125. Conclusions These results provide a potential mechanism of anabolic activity of icariin on BMSCs involving ERK, p38 and JNK MAPK pathways.